Influence of servant leadership and school organizational culture on the performance of public senior high school teachers in Padang city - Fitrah Santosa; Syamsir Syamsir; Afriva Khaidir (Fakultas Ilmu Pendidikan UNP)
Teachers have a very important role in the whole process of achieving the goals of national education. Teachers as educators are required to have maximum performance for the purpose of national education can be achieved. The purpose of this study is to look whether servant leadership and school organizational culture simultaneously influence the performance of public senior high school teacher in Padang City. The research method used is associative quantitative method, data analysis used in this research is regression analysis technique. The research method used is associative quantitative method, the population of this research is teachers of State Senior High School in Padang City, with the number of samples is 292 teachers. The results of this study are: servant leadership and school organizational culture simultaneously have a significant effect on teachers performance at Public Senior High School in Padang City.